1998
DOI: 10.1029/97jd03364
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric near‐surface nitrate at coastal Antarctic sites

Abstract: Sampling Sites and MethodsThe 2. The seasonal change in the occurrence and strength of the surface inversion may contribute to the variability of all short-lived species in the boundary layer except locally produced sea-salt aerosol. As summarized by K6nig-Langlo et al.[this issue], the period from November to February shows a relatively weak or absent surface inversion at NM and DDU but generally stronger temperature gradients at NM (due to radiative cooling). Cyclonic activity, however, may regularly interru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
131
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(155 citation statements)
references
References 65 publications
23
131
1
Order By: Relevance
“…Moderate and low snow accumulation sites including those on the East Antarctic Plateau (EAP) do not preserve the annual cycle well because NO 3 À is reemitted to the atmosphere before it is buried by subsequent snowfall [Goktas et al, 2002;Röthlisberger et al, 2002a]. The annual cycle of nitrate in this study is also similar to that observed in boundary layer air studies at Neumayer, Mawson, Halley, and Dumont d'Urville, and Kohnen Stations [Wagenbach et al, 1998b;Weller and Wagenbach, 2007], although at Neumayer and Mawson the timing of the primary atmospheric peak occurs in November and an additional secondary peak in the fall is typically observed [Wagenbach et al, 1998b].…”
Section: Nitratesupporting
confidence: 71%
See 3 more Smart Citations
“…Moderate and low snow accumulation sites including those on the East Antarctic Plateau (EAP) do not preserve the annual cycle well because NO 3 À is reemitted to the atmosphere before it is buried by subsequent snowfall [Goktas et al, 2002;Röthlisberger et al, 2002a]. The annual cycle of nitrate in this study is also similar to that observed in boundary layer air studies at Neumayer, Mawson, Halley, and Dumont d'Urville, and Kohnen Stations [Wagenbach et al, 1998b;Weller and Wagenbach, 2007], although at Neumayer and Mawson the timing of the primary atmospheric peak occurs in November and an additional secondary peak in the fall is typically observed [Wagenbach et al, 1998b].…”
Section: Nitratesupporting
confidence: 71%
“…The depth of these samples did not exceed 15 m. Figure S4 shows essentially the same pattern at each site in the well-resolved, high-accumulation years of any age. A similar pattern in NO 3 À concentration, with a primary peak in summer and a secondary peak in late winter, has been observed in freshly fallen snow samples from coastal sites at Halley station and Neumayer station Wagenbach et al, 1998b], and from firn and ice core records from Law Dome [Curran et al, 1998;McMorrow et al, 2004]. Moderate and low snow accumulation sites including those on the East Antarctic Plateau (EAP) do not preserve the annual cycle well because NO 3 À is reemitted to the atmosphere before it is buried by subsequent snowfall [Goktas et al, 2002;Röthlisberger et al, 2002a].…”
Section: Nitratementioning
confidence: 60%
See 2 more Smart Citations
“…Nitrate and MSA formation are both dependent on photolytic processes, with MSA being a product of dimethyl sulphide oxidation by OH radicals during abstraction and addition oxidation pathways (von Glasow and Crutzen, 2004). It is thought that most of the nitrate excess (compared to background winter levels) observed during spring and summer originates from sedimentation from the stratosphere, and to a lesser degree (and perhaps latter in the summer season) from photolytic release of nitrate from the snow pack (Wagenbach et al, 1998;Jones et al, 2001;Weller et al, 2004;Savarino et al, 2007). Thus these three independent indicators should give a reliable representation of summer/winter stratification in the snow pit, and can be clearly seen in Fig.…”
Section: Analysis Of Total Iodine From Snow Pit Samplesmentioning
confidence: 99%